Three essays on strategic entrepreneurship in emerging economies - Azevedo, Paulo José de (2024)
This study addresses the strategic entrepreneurship challenges in emerging economies, emphasizing the relevance of the informal economy as a strategic mechanism for entrepreneurs and survival mechanism for people involved in this context. Opportunistic or vulnerable individuals turn to the informal sector as a survival strategy in the face of institutional obstacles, such as bureaucracy and high taxes. This work deepens the understanding of the dynamics between strategic choices of informal and formal companies, the influence of informality on women's professional trajectories and how informality can be linked to illicit practices, highlighting the interaction between the informal economy, entrepreneurship opportunities and socioeconomic challenges.